Improvement of perioperative care of the elderly patient (PeriAge): protocol of a controlled interventional feasibility study - Levente Kriston; Cynthia Olotu; Alwin E Goetz; Rainer Kiefmann; Martin Härter; Lisa Lebherz; Anna Mende; Lili Plümer; Christian Zöllner (BMJ Open)
Introduction Geriatric patients have a pronounced risk to suffer from postoperative complications. While effective risk-specific perioperative measures have been studied in controlled experimental settings, they are rarely found in routine healthcare. This study aims (1) to implement a multicomponent preoperative and intraoperative intervention, and investigate its feasibility, and (2) exploratorily assess the effectiveness of the intervention in routine healthcare.Methods and analysis Feasibility and exploratory effectiveness of the intervention will be investigated in a monocentric, prospective, non-randomised, controlled trial. The intervention includes systematic information for patients and family about measures to prevent postoperative complications; preoperative screening for frailty, malnutrition, strength and mobility with nutrient supplementation and physical exercise (prehabilitation) as needed. Further components focus on potentially inadequate medication, patient blood-management and carbohydrate loading prior to surgery, retainment of orientation aids in the operating room and a geriatric anaesthesia concept. Data will successively be collected from control, implementation and intervention groups. Patients aged 65+ with impending surgery will be included. A sample size of 240, n=80 per group, is planned. Assessments will take place at inclusion and 2, 30 and 180 days after surgery. Mixed-methods analyses will be performed. Exploratory effectiveness will be assessed using mixed segmented regressions. The primary endpoint is functional status. Secondary endpoints include cognitive performance, health-related quality of life, length of inpatient stay and occurrence of postoperative complications. Feasibility will be assessed through semi-structured interviews with staff and patients and quantitative analyses of the data quality, focussing on practicability, acceptance, adoption and fidelity to protocol.Ethics and dissemination The study will be carried out in accordance with the Helsinki Declaration and to principles of good scientific practice. The Ethics Committee of the Medical Association Hamburg, Germany, approved the protocol (study ID: PV5596). Results will be disseminated in scientific journals and healthcare conferences.Trial registration number ClinicalTrials.gov Identifier: NCT03325413.